2012
DOI: 10.1002/pi.4335
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization and thermal degradation of dual temperature‐ and pH‐sensitive RAFT‐made copolymers of N,N‐(dimethylamino)ethyl methacrylate and methyl methacrylate

Abstract: Poly{[(N,N‐(dimethylamino)ethyl methacrylate]‐co‐(methyl methacrylate)} copolymers of various compositions were synthesized by reversible addition‐fragmentation chain transfer (RAFT) polymerization at 70 °C in N,N‐dimethylformamide. The polymer molecular weights and molecular weight distributions were obtained from size exclusion chromatography, and they indicated the controlled nature of the RAFT polymerizations; the polydispersity indices are in the range 1.1–1.3. The reactivity ratios of N,N‐(dimethylamino)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
39
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(49 citation statements)
references
References 65 publications
(70 reference statements)
9
39
0
1
Order By: Relevance
“…In accordance to the results of the kinetic studies, the ratio of the monomers in the isolated copolymers is similar to the initial monomer feed ratio. These results are also in a good agreement with the reported reactivity ratios of MMA and DMAEMA for the RAFT and free radical copolymerizations ( r MMA ∼ 0.8, r DMAEMA ∼ 0.9) . Therefore, it can be concluded that MMA and DMAEMA arrange in the polymer chain in a random sequence.…”
Section: Resultssupporting
confidence: 90%
“…In accordance to the results of the kinetic studies, the ratio of the monomers in the isolated copolymers is similar to the initial monomer feed ratio. These results are also in a good agreement with the reported reactivity ratios of MMA and DMAEMA for the RAFT and free radical copolymerizations ( r MMA ∼ 0.8, r DMAEMA ∼ 0.9) . Therefore, it can be concluded that MMA and DMAEMA arrange in the polymer chain in a random sequence.…”
Section: Resultssupporting
confidence: 90%
“…The peaks in the 1 H NMR spectra that would be indicative of the presence of a vinylic end group were not observed in significant amounts for either the thermolyzed PNIPAm‐ 1 ‐H + or PNIPAm‐ 1 (see Figure S3, Supporting Information). There are few previous investigations of RAFT end group removal from polyacrylamides, in particular poly(NIPAm) or poly( N , N ‐dimethylacrylamide) with trithiocarbonate or dithiobenzoate ends . In the latter case, unsaturated chain ends were also not observed and the NMR spectrum of the product is similar to that seen for thermolyzed PNIPAm‐ 1 .…”
Section: Resultsmentioning
confidence: 90%
“…PMMA‐ 2 ‐H + and PMMA‐ 2 appear unstable with respect to other RAFT‐synthesized PMMA. PMMA with methyl trithiocarbonate or dodecyl trithiocarbonate ends shows end group loss over the temperature range ≈170–220 °C with CS bond homolysis as the dominating mechanism. PMMA with dithiobenzoate ends ≈150–220 °C undergoes end group loss by Chugaev‐type elimination.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, the latter scenario may even produce a copolymer with properties similar to the ones of a homopolymer at the beginning of the chain, which gradually includes more and more of the least reactive monomer. As far as our copolymers are concerned, this, however, did not seem to be the case, with previous literature on MMA/DMAEMA copolymers ( vide infra ) leading two of the Authors to believe that rMMArDMAEMA1, and that copolymers should be expected to present a random comonomer distribution. Such idea was also supported by considerations on the similar electronic structure of the reactive functional groups and the lack of strong intermolecular forces between monomers.…”
Section: Introductionmentioning
confidence: 75%